ANALISIS KESULITAN KEMAMPUAN REPRESENTASI MATEMATIS SISWA EKSTROVERT DALAM MENYELESAIKAN SOAL MATEMATIKA PADA MATERI ALJABAR - Aulia Syafitri; Roseli Theis; Dewi Iriani (Universitas Veteran Bangun Nusantara, 2021)
The objective of this study is to analyze the difficulty of representation ability Mathematical extrovert students in class VII-D in solving math problems on algebraic material, as well as knowing the factors that cause difficulties experienced by students in meet the indicators of mathematical representation ability. The ability of mathematical representations is measured based on Its aspects include visual representation aspects, expression representation aspects mathematics, and aspects of the representation of words or written text. This is qualitative research using a descriptive approach. This is carried out at SMP Negeri 22 Jambi with 4 students from class VII-D. The results showed that SE1, SE2, SE3 and SE4 are students with extrovert personalities do not have difficulty in the visual aspect. On aspects of representation of mathematical equations or expressions of Students SE1, SE3, and SE4 having difficulty making mathematical models or equations. On that aspect word or written text students SE2, SE3, and SE4 have difficulty when determine what steps will be taken to solve the problem mathematical. Factors causing difficulties in the mathematical representation ability are on visual aspects, representational aspects of mathematical expressions, and aspects of word representation or written text is a non-cognitive learning factor